ASSOCIATION OF GASTROESOPHAGEAL REFLUX SYMPTOMS (FREQUENCY AND SEVERITY) WITH BODY MASS INDEX IN FEMALES WITH GASTROESOPHAGEAL REFLUX DISEASE - Arshad Rabbani; Benish Adil; Ramsha Ghazal Arshad (Journal of University Medical & Dental College, 2020)
ABSTRACTBACKGROUND & OBJECTIVE: Overweight individuals have a greater tendency to develop gastroesophageal reflux disease (GERD). This study aims at comparing gastroesophageal reflux symptoms (frequency and severity) in females with different body mass index (BMI) categories.METHODOLOGY: This cross-sectional comparative research study was conducted over duration of 8 months. Both indoor and outdoor patients of medical unit – II Benazir Bhutto Hospital, Rawalpindi, fulfilling the inclusion criteria i.e. females 30-55 years of age with confirmed diagnosis of GERD and informed consent were included. Subjects with history of cigarette smoking, diabetes, use of postmenopausal hormone replacement therapy (HRT), anti-hypertensive or asthma medication were all excluded. Data were collected via proforma and analyzed on SPSS version 17.RESULTS: Among 360 enrolled women, 08 (2.2%) subjects were underweight, 109 (30.3%) had normal BMI, 151 (41.9%) were overweight, 88 (24.4%) subjects were obese and 04 (1.1%) belonged to morbidly obese group. Among 109 subjects with normal BMI, 53 (48.6%) had mild, 40 (36.69%) moderate, 13 (11.9%) severe and 03 (2.75%) very severe GERD. Among 151 overweight subjects, 37 (24.50%) were with mild severity, 64 (42.38%) with moderate, 35 (23.17%) severe and 15 (9.93%) had very severe GERD. Among 04 morbidly obese subjects, 02 (50%) had severe while remaining 02 (50%) had very severe GERD (p=0.000).CONCLUSION: Association of GERD symptoms and BMI were found in both normal and overweight women. Reflux symptoms may be exacerbated or even caused by moderate weight gain in people with normal weight.